2009
DOI: 10.1039/b901192g
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic analogs for evaluating the influence of N–H⋯S hydrogen bonds on the formation of thioester in acetyl coenzyme a synthase

Abstract: A series of square planar methylnickel(II) complexes, (dppe)Ni(Me)(SAr) (dppe = 1,2-bis(diphenylphosphino)ethane); 2. Ar = phenyl; 3. Ar = pentafluorophenyl; 4. Ar = o-pivaloylaminophenyl; 5. Ar = p-pivaloylaminophenyl; (depe)Ni(Me)(SAr), (depe = 1,2-bis(diethylphosphino)ethane); 7. Ar = phenyl; 8. Ar = pentafluorophenyl; 9. Ar = o-pivaloylaminophenyl; 10. Ar = p-pivaloylaminophenyl), were synthesized via the reaction of (dppe)NiMe2(1) and (depe)NiMe2(6) with either the corresponding thiol or disulfide. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…11. Here, the optimized Ni–P distances of 2.24 Å are about 0.1 Å longer than those in the comparable X-ray structures formed by a diphosphine chelate,41 while the P 1 –Ni–P 2 angle of 95.2° is about 8° more open. These aspects are likely the consequence of the already known weaker donor power of the phosphorene P atoms and their strained geometry.…”
Section: Resultsmentioning
confidence: 58%
“…11. Here, the optimized Ni–P distances of 2.24 Å are about 0.1 Å longer than those in the comparable X-ray structures formed by a diphosphine chelate,41 while the P 1 –Ni–P 2 angle of 95.2° is about 8° more open. These aspects are likely the consequence of the already known weaker donor power of the phosphorene P atoms and their strained geometry.…”
Section: Resultsmentioning
confidence: 58%
“…In addition,R iordan has reportedt hat the use of ac omparable nickel(0) complex led to the cleavage of the C acyl ÀSb ond of thioesters containing an electron-deficient C 6 F 5 substituent. [12] We recently reported the synthesis of 2-nickelaoxetanes, [13] prepared from the oxidativea ddition of [{(dtbpe)Ni} 2 (m-h 2 :h 2 -C 6 H 6 )] [14] (1)( dtbpe = 1,2-bis(di-tert-butyl)phosphinoethane) onto epoxidest hat bear aketone group. Our mechanisticstudies indicated that the precoordinationo ft he metal centre to the carbonyl of the epoxide was crucial for the reaction to occur.W et hus soughtt oe xplore what other transformations could be enabled by precoordinationo fareactive, low-valent nickel centre to ac arbonyl fragment of organic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Upon heating, CO is released and activation of a second equivalent of thioester led to a platinum dithiolate complex. In addition, Riordan has reported that the use of a comparable nickel(0) complex led to the cleavage of the C acyl −S bond of thioesters containing an electron‐deficient C 6 F 5 substituent …”
Section: Introductionmentioning
confidence: 99%
“…PtÀCH 3 appeared in the 13 C{ 1 H} NMR spectrum as a doublet of doublets with platinum satellites at δ À4.96 (J PÀC = 7.7 Hz, J PÀC = 87. 6 Hz, J PtÀC = 534.5 Hz). In the 1 H NMR spectrum, the methyl resonance was obscured by overlap with the isopropyl resonances (confirmed by HSQC NMR spectroscopy).…”
Section: Articlementioning
confidence: 94%
“…In the 31 P{ 1 H} NMR spectrum, 8 appears as a singlet with platinum satellites at δ 66.25 ( 1 J PtÀP = 2747 Hz, 3 J PtÀP = 64. 6 Hz, 3 J PÀP-trans = 24.1 Hz, 3 J PÀP-cis = 8. 3 Hz).…”
Section: Articlementioning
confidence: 98%